Euphemism Analysis on Retno Marsudi’ Speech at the 2024 ICJ Public Sitting - Setyawan, Agustinus Hary; Khuzaini, Nanang (Deskripsi Bahasa, 2025)
This research discusses the euphemism in the oral statement of the Minister of Foreign Affairs of the Republic of Indonesia in 2014 at the Public Sitting of the International Court of Justice on The Legal Consequences Arising from The Policies and Practices of Israel in The Occupied Palestine. This research aimed to find out how types of euphemisms are used and find out their purpose. The method used was a qualitative method with data in the form of Retno Marusudi's verbal statement. The data were analyzed using the warren framework to determine the type and function of the euphemism uttered. This research resulted in Compounding (10.5%), derivation (10.5%), Blends (5.26%), acronyms (5.26%), and abbreviations (5.26%) as part of word formation. Phonemic modification is represented by abbreviations, appearing once at 5.26%. The speech utilized a variety of semantic innovation strategies: particularization, implication, metaphor, metonymy, and understatement each appear twice, accounting for 10.53% each. Reversal/irony and overstatement were used once, each constituting 5.26%. The way euphemistic functions were distributed in Marsudi's discourse showed that coherent, provocative, underhanded, and protecting euphemisms were all used in moderation. The percentage of protective euphemisms was 21.1%; the percentage of underhanded and cohesive euphemisms is 15.8%; the percentage of provocative euphemisms was 31.6%; the percentage of uplifting and ludic euphemisms was less, at 5.3% and 10.5%, respectively. The use of euphemisms aims to convey a strong yet diplomatic message, highlight political and legal sensitivities, and emphasize urgency and injustice so that the message conveyed remains firm yet expressed subtly, clarifying Indonesia's diplomatic position while provoking understanding and emotional responses from the audience.